Ethnicity as a cultural factor influencing complete vaccination among children aged 12-23 months in Nigeria - Rotimi Felix Afolabi; Mobolaji M. Salawu; Babatunde Makinde Gbadebo; Adetokunbo T. Salawu; Adeniyi Francis Fagbamigbe; Ayo Stephen Adebowale (Taylor & Francis Group, 2021)
Achieving complete vaccination for children has been challenging in Nigeria. Yet, addressing Nigeria's completeness of vaccination requires ethno-cultural diversity consideration rather than nationally population based. This study explored patterns and determinants of complete vaccination among children of Hausa/Fulani, Igbo and Yoruba, the predominant ethnicities in Nigeria. The study used a cross-sectional data involving 3980 children aged 12-23 months extracted from the 2018 Nigeria Demographic and Health Survey dataset. In this study, complete vaccination is defined as a child who received all recommended vaccinations. A generalized linear mixed model applied to clustered data was used for data analysis (α = 0.05). The prevalence of complete vaccinations was 56.3%, 40.8% and 18.2% among Igbo, Yoruba and Hausa/Fulani children, respectively. The likelihood of complete vaccination was higher among children who were of Igbo (aOR = 1.38; CI: 1.20-1.59) compared with Hausa/Fulani. Predictors of complete vaccination were maternal age-at-childbirth, education, prenatal-care attendant and place of delivery among Hausa/Fulani; place of residence and perceived access to self-medical help, among Igbo; while prenatal-care attendance, among Yoruba. The odds of complete vaccination were higher among Hausa/Fulani (aOR = 1.65; CI: 1.04-2.61), Igbo (aOR = 2.55; CI: 1.20-5.44) and Yoruba (aOR = 4.22; CI: 1.27-13.96) children from higher wealth-quintile households compared to those from poor households. There was evidence of variability in the likelihood of complete vaccination in all the ethnic groups. The Hausa/Fulani tribe had the lowest complete vaccination coverage for children aged 12-23 months. Context-specific program intervention to improve complete vaccination is needed to ensure that the SDG target for vaccination is met.